Spectrum of chronic kidney disease in China: A national study based on hospitalized patients from 2010 to 2015. Issue 7 (30th April 2019) - Huang, Yu‐Ming; Xu, Damin; Long, Jianyan; Shi, Ying; Zhang, Luxia; Wang, Haibo; Levin, Adeera; Zhao, Ming‐Hui
ABSTRACT: Aim: To investigate the spectrum of chronic kidney disease (CKD) in China. Methods: We used a large national in‐patient database covering 878 class three hospitals and involving 64.7 million adult patients in China from 2010 to 2015. The class 3 hospital in China is ranked as the top tier of medical system in China with at least 500 beds and the accreditation from health authorities. The specific causes of CKD were extracted from the International Classification of Diseases‐10 codes of discharge diagnoses. Results: A total of 4.5% of hospitalized patients (1.8 million) were identified as CKD, with an increased percentage from 2010 (3.7%) to 2015 (4.7%). Increasing trends of diabetic kidney disease and hypertensive nephropathy were observed from 2010 to 2015 (19.5% vs 24.3% and 11.5% vs 15.9%, respectively), especially for urban residents from north China. The proportion of obstructive nephropathy also increased gradually (10.3% in 2010 vs 15.6% in 2015) and constituted another important cause of CKD for patients, especially for those from south China and rural residents. Conclusion: The spectrum of CKD is changing in China, with variations over time and geographic regions, which has implication regarding developing the prevention strategy of CKD. Summary at a Glance: The authors used a large hospitalization database to estimate the prevalence and causes of chronic kidney disease (CKD) in China from 2010 to 2015. Overall 4.5% of hospitalized patients were identified as having CKD, although this is likely an underestimation due to coding limitations.